Obesity Does Not Modify the Risk of Differentiated Thyroid Cancer in a Cytological Series of Thyroid Nodules. Issue 2 (27th July 2016) - Rotondi, Mario; Castagna, Maria Grazia; Cappelli, Carlo; Ciuoli, Cristina; Coperchini, Francesca; Chiofalo, Francesco; Maino, Fabio; Palmitesta, Paola; Chiovato, Luca; Pacini, Furio
Abstract : Background: A possible impact of obesity on the risk of thyroid cancer has been postulated in some studies, but it remains controversial. Objective: To investigate the association between obesity and differentiated thyroid carcinoma in a population of unselected patients subjected to fine-needle aspiration cytology (FNAC) for thyroid nodules. Methods: We retrospectively evaluated the results of FNAC of thyroid nodules in 4, 849 patients (3, 809 females and 1, 040 males; mean age 55.9 ± 14.1 years). Patients were stratified according to their body mass index (BMI). There were 1, 876 (38.7%) normal-weight patients (BMI 18-24.9), 1, 758 (36.2%) overweight (BMI 25-29.9), 662 (13.7%) grade 1 obese (BMI 30-34.9), 310 (6.4%) grade 2 obese (BMI 35-39.9) and 243 (5.0%) grade 3 obese (BMI >40). Results: The prevalence of suspicious or malignant nodules (Thy4/Thy5) did not differ across the 5 BMI groups, i.e. it was 6.8% in normal-weight patients, 6.3% in overweight patients, 6.3% in grade 1 obese patients, 4.0% in grade 2 obese patients and 4.2% in grade 3 obese patients (p = 0.29). The prevalence of Thy4/Thy5 nodules did not differ when males and females were evaluated separately (p = 0.22 and p = 0.12, respectively). A significant, lower rate of Thy4/5 cytology was observed in female patients with grade 2-3 obesity (odds ratio 0.51; 95% confidence interval 0.284-0.920; p = 0.009). Conclusions: The results of this study, in a retrospective series of patients with thyroid nodules, do not confirm previous findings reporting an association between obesity and differentiated thyroid carcinoma. Thus, obese patients with nodular thyroid disease should be managed the same as normal-weight patients.